Using communication to boost vaccination: Lessons for COVID-19 from evaluations of eight large-scale programs to promote routine vaccinations - Kappes, Heather Barry; Toma, Mattie; Balu, Rekha; Burnett, Russ; Chen, Nuole; Johnson, Rebecca; Leight, Jessica; Omer, Saad B.; Safran, Elana; Steffel, Mary; Trump, Kris-Stella; Yokum, David; et al. (SAGE Publications, 2023)
The COVID-19 pandemic has added new urgency to the question of how best to motivate people to get needed vaccines. In this article, we present lessons gleaned from government evaluations of eight large randomized controlled trials of interventions that used direct communications to increase the uptake of routine vaccines. These evaluations, conducted by the U.S. General Services Administration’s Office of Evaluation Sciences (OES) before the start of the pandemic, had a median sample size of 55,000. Participating organizations deployed a variety of behaviorally informed direct communications and used administrative data to measure whether people who received the communications got vaccinated or took steps toward vaccination. The results of six of the eight evaluations were not statistically significant, and a meta-analysis suggests that changes in vaccination rates ranged from -0.004 to 0.394 percentage points. The remaining two evaluations yielded increases in vaccination rates that were statistically significant, albeit modest: 0.59 and 0.16 percentage points. Agencies looking for cost-effective ways to use communications to boost vaccine uptake in the field—whether for COVID-19 or for other diseases-may want to evaluate program effectiveness early on so messages and methods may be adjusted as needed, and they should expect effects to be smaller than those seen in academic studies.